Fundamental Movement Skills and Their Assessment in Primary Schools from the Perspective of Teachers - Eddy, Lucy; Hill, Liam J.B.; Mon-Williams, Mark; Preston, Nick; Daly-Smith, Andy; Medd, Gareth; Bingham, Daniel D. (Measurement in physical education and exercise science, 2021)
Evidence suggests that children struggle to acquire age-appropriate fundamental movement skills (FMS), despite their importance for facilitating physical activity. This has led to calls for routine school-based screening of children's FMS. However, there is limited research exploring schools' capacity to conduct such assessments. This study investigated what factors might affect the adoption and implementation of FMS assessments in primary schools. School staff (n = 853) completed an online questionnaire developed using the Capability, Opportunity, Motivation and Behavior (COM-B) model. A majority reported that knowledge of pupils' FMS ability would be beneficial (65.3%), and 71.8% would assess FMS if support was provided. Barriers included: Capability - few possessed knowledge of FMS (15%); Opportunity - teachers reported 30-60 minutes as acceptable for assessing a class, a substantially shorter period than current assessments require; Motivation - 57.2% stated FMS assessments would increase workload stress. Solutions to these issues are discussed using the COM-B theoretical framework.